THE NETWORK OF ULAMA IN LAMPUNG: TRACING THE ISLAMIC DEVELOPMENT AND ITS INFLUENCE ON LOCAL TRADITION AND CULTURE - Abidin, Zainal; Basri, Basri; Nopriyana, Rahma Dwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2020)
This article is aimed at depicting the spread of Islam by ulama in introducing and disseminating Islam in Lampung. This article points to the three theories of the spread of Islam in Lampung. First, the theory states that Islam was originated in Banten. The second theory claims that Islam came from Pagaruyung West Sumatra through the west Lampung region. The third theory maintains that Islam was carried by Ulama from Palembang then spread from the north of Lampung. This article also confirms the contribution of Lampung ulamas. These Islamic spreaders' arrival ran accommodatingly without opposing local tradition and culture that are in line with the basic principles of Islamic teachings. The arrival of Islam enriched Piil Pesenggiri's philosophy, Pegung Pakai philosophy, and other cultural traditions. Islamic dissemination ulamas in Lampung have different backgrounds in terms of motives of the spread and their origins. The deployment strategy is done individually as well as organized. The ulama have a network with the sultanate's political power and dealing with local rulers in Lampung. This relationship was reflected in political, economic, and familial agreements or kinship relationships through marriage between noble families from Banten and Lampung. This relationship has an impact on strengthening emotional bonds in the Islamicization process in Lampung.